The use of wearable technology to quantify power and muscle load differences during running against varying wind resistances - Bello, M. L.; Anglin, D. A.; Gillen, Z. M.; Smith, J. E. W. (International Journal of Kinesiology & Sports Science, 2022)
Background: Wearable technology has increased in popularity due to its live feedback and ability to adjust within training sessions. In addition to heart rate (HR) monitoring, measuring power and internal load may provide useful insight and a more comprehensive view of training differences. Objectives: Assess the efficacy of wearable technology in endurance runners to determine changes in performance variables with varying wind resistance. Methods: A quasi-experimental study was designed and recruited twelve endurance-trained runners currently running =120 min/week for the past 3 months. Participants completed two sessions: V?O2peak testing, and a 20-min run at 70% V?O2peak. The run was evenly divided into no wind resistance (W0) and 16.1 km/h wind resistance (W16). Power was assessed via a power meter and internal/external load measured via surface EMG sensor-embedded compression shorts. A HR sensor was used and V?O2 and RER were monitored using a metabolic cart. Paired t-tests were used to compare differences and Pearson correlations were conducted for each segment. Significance was set a priori at p<0.05. Results: There were significant differences in power (W16 > W0; p=0.002), as well as a strong positive correlation between power and internal load for W0 (r=0.692; p=0.013) and W16 (r=0.657; p=0.02). Conclusions: The lack of significance changes in HR, V?O2, and RER demonstrates a sustained similar physiological response. The significant increase observed in power suggests the power meter can be useful in differentiating wind resistance, and the positive correlations suggest a combination of these devices may be beneficial in distinguishing performance changes during fluctuating conditions.